Clinical outcomes of thyroid tumours with concurrent epithelial and mesenchymal components in 14 dogs (2006–2020). Issue 2 (3rd February 2022) - Cook, Matthew R.; Gasparini, Molly; Cianciolo, Rachel E.; Brown, Megan E.; Moore, Antony S.; Curran, Kaitlin M.; Maxwell, Elizabeth A.; Gasson, Shelby; Wustefeld‐Janssenss, Brandan G.; Veluvolu, Sridhar M.; Keepman, Samuel; Wouda, Raelene; et al.
Abstract: Background: While rare, multiple individual case reports have described mixed thyroid tumours in dogs containing both epithelial and mesenchymal neoplastic components. Objectives: In this retrospective case series, we describe the clinical presentation, treatment and outcome of 14 dogs of canine thyroid tumours with concurrent mesenchymal and epithelial neoplastic populations. Methods: Fourteen cases were retrospectively abstracted from nine institutions. Histopathologic samples and reports were collected from 10/14 dogs and reviewed by a single board‐certified anatomic pathologist. Results: All 14 dogs had curative‐intent surgery to remove the thyroid neoplasm. The most common surgery performed was a unilateral thyroidectomy (10/14 dogs). Postoperatively, systemic therapy was administered in eight dogs. Six dogs developed local recurrence with a median time to loco‐regional recurrence of 53 days. Ten dogs developed metastatic disease with the most common metastatic site being the lungs (6/10 dogs), with a median time to metastasis of 93 days. Ten dogs were euthanised due to locoregional or distant progression of their mixed thyroid neoplasm. The overall median survival time was 156 days (95%CI: 49–244). The median survival time for dogs treated with adjuvant therapy was 189 days (95%CI: 24–244), whereas dogs without adjuvant therapy had a median survival time of 156 days (95%CI: 35‐upper limit could not be calculated; p  = 0.62). Conclusion: The thyroid tumours with both mesenchymal and epithelial components in this small sample set were associated with a poor prognosis after surgical excision with or without adjunctive therapy. Abstract : The purpose of this retrospective case series was to describe the clinical behaviour, features, diagnosis, treatment and outcomes in a larger cohort of dogs diagnosed with malignant mixed thyroid tumours, specifically evaluating measures of outcomes following primary surgical excision, with or without adjunctive systemic therapy.